PENGARUH MEDIA WEBSITE BASED LEARNING WORD-WALL TERHADAP HASIL BELAJAR KOSAKATA BAHASA ARAB SISWA SEKOLAH DASAR - Hanna Rosyada; Muh. Fajar Shodiq (Tanfidziya: Journal of Arabic Education, 2024)
Language learning, including Arabic, is essential in the modern era as a means of communication. Arabic has been taught in various formal educational institutions due to its relevance from an early age. The success of teaching depends on using media suited to students' characteristics. Appropriate learning media can encourage active participation and enhance material comprehension. One innovative medium utilized in this study is Wordwall, applied to improve Arabic vocabulary mastery. This research employed a quantitative method with a Quasi-Experimental design in the form of a Nonequivalent Control Group Design. The primary objective was to determine the effect of using Wordwall media on students' learning outcomes. Data were collected through tests, observations, interviews, and documentation. The study results revealed that students in the control class (without Wordwall) experienced an average score increase of 20.6 points, from 67.4 to 88. Meanwhile, students in the experimental class (using Wordwall) achieved a more significant improvement of 23.6 points, from 74.2 to 97.8. Hypothesis testing confirmed a significant influence of Wordwall on students' learning outcomes, with tcount>ttablet_{count} > t_{table}tcount​>ttable​ (0.05 > 0.003). This study concludes that Wordwall is effective in enhancing Arabic vocabulary mastery and serves as an innovative learning alternative relevant to the needs of modern students. Keywords: Word Wall, Learning Media, Learning Results, Arabic Mufroda̅t